Understanding commitment to agroforestry - Ibrahim, Fausat Motunrayo (Acta silvae et ligni, 2023)
Agroforestry is strategic in reconciling food production with forest biodiversity conservation. The methodical investigation of the beneficial and ecological imperativeness that informs smallholder farmers’ commitment to agroforestry is called for. This work is therefore an attempt to examine the relative importance of farmers' attitudes towards forest loss and perceived benefits of agroforestry in farmers' commitment to agroforestry among a group of farmers in Oyo State, southwestern Nigeria. The study is a cross-sectional survey that featured the interview administration of 400 structured questionnaires among crop farmers that were selected through clustered purposive sampling. Respondent’s agreement with sets of relevant statements was elicited and used in the assessment of variables. Independent samples t-test and one-way ANOVA were used to examine the significance of the difference in respondents’ commitment to agroforestry across sub-groups of gender and age/education respectively. The Pearson correlation coefficient was used to examine the relationship between variables. Results indicate that 57.8% exhibited a 'high' commitment to agroforestry. Gender, age and education had main effects on commitment (p 0.05) but not perceived benefits (r = 0.426, p < 0.05). Being male, middle-aged and poorly educated are significantly more predisposing to exhibiting lower commitment to agroforestry. There is hardly an ecological or forest restoration motivation for agroforestry in the study area. Ecologically smart agriculture or the restorative importance of agroforestry appears to be poorly entrenched among farmers in the study area.
Keywords: agroforestry; attitude; commitment; forest loss; kmetijsko-gozdarski sistemi; Nigeria; Nigerija; odnos; perception; predanost; zaznava; zguba gozdov